Optimalisasi Menggunakan Access Control List Berbasis Mikrotik pada Amami Event Organizer - Amar, Mohammad Rosihin; Anwar, Saeful; Nurdiawan, Odi (LPPM UNIKA Santo Thomas Medan, 2022)
Technological developments can be used as a medium for disseminating information in order to market products and services. One of them is Amami event organizer, which is a company engaged in services for exhibition events. The company, which is located in the city of Cirebon, has utilized internet services as part of a campaign in their business marketing strategy. The use of the internet network itself cannot be separated from the existence of a problem, and one of them is regarding the quality of the existing network at the Amami event organizer. where there is no bandwidth management that regulates the distribution of bandwidth evenly which includes downloads and uploads, bandwidth management itself is a method for managing bandwidth limits given to a data traffic. Not only the problem of bandwidth management, another problem that the management of Amami event organizers complains about is the lack of control of internet network users in accessing certain websites so that it can interfere with work productivity and smooth use of the internet network. The solution to the problem that is carried out to overcome the problem of bandwidth management is the hotspot user method. Which users will be classified into several groups with the aim of managing bandwidth based on user logins. For user control problems, a filtering address list is used through the firewall features in Mikrotik to filter out which sites cannot be accessed by the user. This study analyzes the quality of internet network services after using the hotspot user method and using the filtering address list method. To measure the quality of the internet network, measurements are used using Quality of Service (QoS) such as throughput, jitter, packet loss, and delay. To measure QoS, a wireshark tool is needed which the tool can capture traffic. From the optimization results obtained quite good results, namely the measurement results can be seen from testing through stable QoS throughput > 1000 kbps, packet loss to 0% maximum at 2%, delay < 300 ms, and the highest Jitter at 2297 ms while the lowest at 0.001 Ms. Therefore, the thing that needs to be done by the Amami event organizer is to do bandwidth management to regulate the distribution of bandwidth for each user. As well as restricting user site access to a certain website